Normalization of serum TSH doesn’t represent true euthyroidism for patients on levothyroxine treatment - Nalan Okuroglu; Sakci, Elif; Sertbas, Meltem; Sertbas, Yasar; Sancak, Seda; Ozdemir, Ali (Journal of the Pakistan Medical Association, 2022)
Introduction: To evaluate whether normalisation of serum thyroid-stimulating hormonelevels with levothyroxine is related with metabolic parameters and psychologic wellbeing. Method: The observational, case-control study was conducted from to May to July 2019 in the outpatient thyroid clinics of Fatih Sultan Mehmet Education and Research Hospital, Istanbul, Turkey, and compried hypothyroid patients in the euthyroid state with levothyroxine treatment and euthyroid controls. Psychological wellbeing was assessed using the General Health Questionnaire-12, and metabolic parameters with lipid levels and body composition were analysed for both the groups. Data was analysed using SPSS 25. Results: Of the 159 subjects, 110(69%) were case with a mean age of 50.1±11.7 years, and 49(31%) were controls with a mean age of 47.3±15.2 years. There was no significant difference related to thyroid-stimulating hormonel levels between the groups (p=0.191). Free throxine levels were significantly higher in the cases, while free triiodothyroinine levels were higher in the controls (p<0.001). Total cholesterol and triglycerides levels were significantly higher in the cases than the controls (p<0.05). The cases had lower basal metabolic rate and fat free mass than the controls, but the difference was not significant (p>0.05). The cases scored higher in terms of wellbeing than the controls, but the difference was not significant (p>0.05). Conclusion: Thyroid hormone replacement needs to be adjusted to provide a satisfactory treatment for hypothyroid patients with normal thyroid-stimulating hormone levels who remain clinically and biochemically asymptomatic. In symptomatic patients, peripheral parameters of hypothyroidism, such as lipid levels, ---Continue